2021
DOI: 10.3390/ijerph182211736
|View full text |Cite
|
Sign up to set email alerts
|

College Satisfaction, Sense of Achievement, Student Happiness and Sense of Belonging of Freshmen in Chinese Private Colleges: Mediation Effect of Emotion Regulation

Abstract: Sense of belonging constitutes a critical component of college students’ retention and academic achievement, especially in disadvantaged higher education institutions such as private colleges in China. Using nationwide survey data (n = 3816) from Chinese private colleges, this study explores how college satisfaction, sense of achievement, and student happiness contribute to freshmen’ sense of belonging. Structural equation modeling analyses have identified the significant positive associations between freshmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
3
6
0
Order By: Relevance
“…This study shows that perceived support was significantly and negatively correlated with nursing students’ academic stress ( r = − 0.236, p < 0.01), which is consistent with the findings of Tian et al [ 36 ], who found that good support can increase a student’s sense of belonging, decrease academic burnout, and motivate them to learn, thereby reducing their academic stress. Secondly, the study revealed that social support was significantly and negatively related to self-regulatory fatigue ( r = − 0.190, p < 0.01), which is consistent with the findings of my previous study on nursing staff, which indicated that social support can somehow compensate for the depletion of emotional resources and thus mitigate the negative utility of emotional depletion [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…This study shows that perceived support was significantly and negatively correlated with nursing students’ academic stress ( r = − 0.236, p < 0.01), which is consistent with the findings of Tian et al [ 36 ], who found that good support can increase a student’s sense of belonging, decrease academic burnout, and motivate them to learn, thereby reducing their academic stress. Secondly, the study revealed that social support was significantly and negatively related to self-regulatory fatigue ( r = − 0.190, p < 0.01), which is consistent with the findings of my previous study on nursing staff, which indicated that social support can somehow compensate for the depletion of emotional resources and thus mitigate the negative utility of emotional depletion [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this study also show that learning satisfaction plays an intermediary role in the emotion regulation and psychological capital of university students, supporting Hypothesis 2. Previous studies have found correlations between emotion regulation and satisfaction [ 88 , 89 ] and between satisfaction and psychological capital [ 90 , 91 ], and these relationships were supported in the present study. Emotion regulation can help relieve stress, reduce negative emotions, and improve satisfaction.…”
Section: Discussionsupporting
confidence: 89%
“…In this context, as the conditions change, the sense of belonging may change, and even fluctuations can be observed from moment to moment (Gillen-O'Neel, 2021). Studies on the effect of feeling of belonging on wellbeing and mental health were well documented (Arslan, 2021;Tian et al, 2021;Wang et al, 2016;Zhou et al, 2022) that the findings of the current study extend the existing research by demonstrating the partial mediation role of social connectedness on this relationship.…”
Section: Journal Of Happiness and Healthsupporting
confidence: 76%
“…Wellbeing is a complex concept that includes different components such as happiness, flourishing, vitality, life satisfaction, quality of life, and prosperity. Tian et al (2021) argued happiness which is used interchangeably with wellbeing is vital component in facilitating students' sense of belonging. Although university students' wellbeing is significantly differed by gender, socioeconomic status, and academic achievement, the sense of university belonging is positively correlated with life satisfaction (Wang et al, 2016).…”
mentioning
confidence: 99%